CURRENT PERSPECTIVES ON THE PHYSIOTHERAPIST PROFESSIONAL AND THEIR ROLE IN AESTHETICS (REMUNOM, 2024)
The purpose of this academic article is to address current perspectives on professional physiotherapists and their role in aesthetics, highlighting the historical evolution of physiotherapy in this context, dermatofunctional physiotherapy, current legislation and the areas of activity of physiotherapists. To this end, a bibliographical research was carried out, based on scientific articles, books, legislation and websites related to dermatofunctional physiotherapy and its role in aesthetics. In the end, it is expected to demonstrate the important role played by the dermatofunctional physiotherapist in promoting the health and well-being of patients, as he contributes not only to the improvement of aesthetic appearance, but also to the restoration of bodily function and the promoting self-esteem and quality of life.